Reconsidering Openness in Organizational Communication - Eisenberg, Eric M.; Witten, Marsha G. (Academy of Management Review, 1987)
Much organizational theory and research is characterized by an uncritical acceptance of the efficacy of open communication. In this critique, the lack of support for this view of openness is discussed. A contingency perspective that more accurately reflects the political nature of organizational life is proposed.